Technology Enhancement and Ethics In the Paralympic Games - Βουρνά, Σταυρούλα (Πανεπιστήμιο Πελοποννήσου, 2016)
The aim of the present thesis is to present how the new technological advances can affect the performance of the athletes in the Paralympic Games. The main question that this paper aspires to address is whether the evolution of technology enables the athletes’ natural performance or if it is used mainly for the enhancement of their performances. It is also mentioned how much technology should be allowed in the Paralympic Games and how the results of the games are being technology-dependent. In order to achieve this goal the essay includes references to the meaning of the Paralympic Games, what is disability, in which categories are separated through their impairment, what is the classification system according their impairment and the history of the games. Furthermore, it mentions the International Paralympic Committee-IPC, the creation of it, the core and the values behind that idea, the motto and the mission regarding the educational and developmental strategy of the IPC. In the second part, it is being analyzed the term techno doping and if the evolution of technology is being used by the athletes for a natural performance or for the enhancement of their existing performance. It is also being discussed a possible advantage of disabled athletes by using prosthetics in "normal" competitions, and how to be included in such competitions concerning the gradual improvement of technical aids. The results showed that due to technology improvement, International Paralympic Committee shall always mark the assistive devices of each athlete and set rules and regulations concerning them in a regular basis.
Keywords: Paralympic Games; Olympism; Olympics - Philosophy; Παραολυμπιακοί Αγώνες; Ολυμπισμός; Ολυμπιακοί αγώνες - Φιλοσοφία; Technology enhancement; Techno-doping; Paralympic Games; Ethics; Assistive devices in sports; Βελτίωση τεχνολογίας; Τεχνολογία - ντόπινγκ; Παραολυμπιακοί Αγώνες; Υποστηρικτικές συσκευές στον αθλητισμό